PROGRAM EDUKASI MEMBANGUN KESADARAN PELAJAR TERHADAP BAHAYA TERORISME DI SD NEGERI 035 TARAI BANGUN - Agustina Fransiska Marbun; Sintia Futri; Miftahul Jannah; Dian Purkan; Ilham Hudi (CV. Denasya Smart Publisher, 2026)
This community service program was conducted to enhance students’ understanding and awareness at SD Negeri 035 Tarai Bangun regarding the prevention of violent behavior through an educational outreach approach. Terrorism represents a complex and multidimensional global threat that continues to evolve and poses risks of violence and social instability. Accordingly, this program aimed to introduce early prevention strategies by strengthening students’ knowledge and values related to peace, tolerance, and critical thinking. The methods employed included preliminary observation, delivery of educational materials, interactive discussions, and a simple evaluation to assess students’ comprehension. The outreach activities targeted elementary school students as a vulnerable group that requires early educational intervention to prevent exposure to violent and extremist ideologies. The results demonstrated an improvement in students’ understanding following the program, as reflected in satisfactory post-activity quiz outcomes. These findings indicate that educational socialization is an effective early preventive strategy to equip students with essential knowledge and critical attitudes to reject violence, terrorism, and radicalism.